1989
DOI: 10.1177/002224298905300105
|View full text |Cite
|
Sign up to set email alerts
|

Dealer Dependence Levels and Reciprocal Actions in a Channel of Distribution in a Developing Country

Abstract: The primary purpose of this article is to expand our understanding of the dependence and reciprocal action constructs in distribution channel relationships. The authors develop a conceptual framework for channel relationships involving the exchange of industrial products within sellers' markets in developing countries. The framework is tested with data collected in the tungsten carbide tool industry in India. Results are generally supportive of the conceptual framework and illustrate the need to (1) take the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
12

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(126 citation statements)
references
References 48 publications
5
109
0
12
Order By: Relevance
“…The specific items used to assess each party's level of dependence (see Appendix B) were adaptations of items used in prior studies of inter-organizational dependence (Frazier and Rody 1991, Gulati and Sytch 2007, Kumar et al 1998 to represent the concentration of the exchange, the availability of alternatives, and the level of relationship-specific investments. Several prior studies have modeled inter-organizational dependence as a formative rather than a reflective construct (e.g., El-Ansary and Stern 1972, Frazier et al 1989, Howell 1987, Kumar et al 1998), and we follow this precedent. In deciding whether to model a construct as reflective or formative, it is advised that researchers ask two related questions (Bollen 2011, Bollen and Lennox 1991, Diamantopoulos and Winklhofer 2001, MacCallum and Browne 1993: (i) Do the indicators (i.e., items) represent a unidimensional concept?…”
Section: Measurementmentioning
confidence: 95%
“…The specific items used to assess each party's level of dependence (see Appendix B) were adaptations of items used in prior studies of inter-organizational dependence (Frazier and Rody 1991, Gulati and Sytch 2007, Kumar et al 1998 to represent the concentration of the exchange, the availability of alternatives, and the level of relationship-specific investments. Several prior studies have modeled inter-organizational dependence as a formative rather than a reflective construct (e.g., El-Ansary and Stern 1972, Frazier et al 1989, Howell 1987, Kumar et al 1998), and we follow this precedent. In deciding whether to model a construct as reflective or formative, it is advised that researchers ask two related questions (Bollen 2011, Bollen and Lennox 1991, Diamantopoulos and Winklhofer 2001, MacCallum and Browne 1993: (i) Do the indicators (i.e., items) represent a unidimensional concept?…”
Section: Measurementmentioning
confidence: 95%
“…All constructs included in this study were measured using multi-item scales adapted from prior studies (Frazier, Gill, and Kale 1989;Ganesan 1994;Sako and Helper 1998) (see Appendix for comprehensive scale items). In the questionnaire, respondents were asked to think about the supplier of a new product added within the last year; if they carried several new products, they were asked to focus on the supplier that represented the greatest portion of their buying.…”
Section: Measurementmentioning
confidence: 99%
“…For instance, Provan and Skinner (1989) found that dealers of agricultural equipment were less opportunistic when they depended on a primary supplier, whereas suppliers with greater control over dealers' decisions exhibited greater opportunism. Also, Frazier, Gill and Kale (1989) posit that firms often employ a number of coercive influences on trading partners under various conditions of dependence, including threats, promises, and legalistic pleas. A later study by Smith and Aldrich (1991) found that greater levels of trust between buyers and suppliers resulted in fewer bureaucratic controls, but only when mediated through information sharing.…”
Section: Theoretical Motivation: the Dynamics Of Asymmetrical Powermentioning
confidence: 99%